The Evolution of AGB Stars on Infrared 2-Color Diagrams - Kyung-Won Suh; Jae Woo Lee; Hak-Youn Kim (Journal of Astronomy and Space Sciences, 2001)
We present infrared 2-color diagrams of AGB stars from the observations at near infrared and IRAS point source catalog (PSC) data. We compile the observations for thousands of newly identified OH/IR stars and carbon stars. We compare the observations with the theoretical evolutionary tracks of AGB stars. From the new observational data base and theoretical tracks, we discuss the meaning of the infrared 2-color diagrams.